2016
DOI: 10.1373/clinchem.2015.251835
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Serial Changes in High-Sensitivity Cardiac Troponin I and T over 3 Months Using Reference Change Values in Hemodialysis Patients

Abstract: INTRODUCTION:Serial changes in cardiac troponin in hemodialysis (HD) patients have uncertain clinical implications. We evaluated associations of adverse outcomes in HD patients with reference change value (RCV) data and tertile concentrations for cardiac troponin I (cTnI) and cTnT measured by high-sensitivity (hs) assays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
30
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(34 citation statements)
references
References 24 publications
(35 reference statements)
1
30
1
Order By: Relevance
“…The 180-day mortality with respect to hs-cTnI by tertile (0-2.5 ng/ml [tertile 1; n=546], 2.5-10.6 ng/L [tertile 2; n=555], and .10.6 ng/L (tertile 3; n=539]) for all patients is shown in Figure 1. Mortality increased significantly with increasing 13,0.001 MI at presentation, high sensitivity, n (%) 167 (11) 49 750 (11) 41 18) (2110 13,0.001 MI at presentation, contemporary, n (%) 205 (13) 72 (10) 61 1446 20 hs-cTnI tertile: 1.3% (seven patients), 6.0% (33 patients), and 10.4% (56 patients), respectively (P,0.001 for tertile 1 versus 2 and tertile 1 versus 3 and P,0.01 for tertile 2 versus 3). The 180-day mortality with respect to hs-cTnI groups defined by concentrations less than limit of detection (LoD; n=445), LoD to less than sex-specific upper reference limits (URLs; n=886), and greater then sex-specific URLs (n=309) is shown in Figure 2.…”
Section: Significance Statementmentioning
confidence: 98%
See 2 more Smart Citations
“…The 180-day mortality with respect to hs-cTnI by tertile (0-2.5 ng/ml [tertile 1; n=546], 2.5-10.6 ng/L [tertile 2; n=555], and .10.6 ng/L (tertile 3; n=539]) for all patients is shown in Figure 1. Mortality increased significantly with increasing 13,0.001 MI at presentation, high sensitivity, n (%) 167 (11) 49 750 (11) 41 18) (2110 13,0.001 MI at presentation, contemporary, n (%) 205 (13) 72 (10) 61 1446 20 hs-cTnI tertile: 1.3% (seven patients), 6.0% (33 patients), and 10.4% (56 patients), respectively (P,0.001 for tertile 1 versus 2 and tertile 1 versus 3 and P,0.01 for tertile 2 versus 3). The 180-day mortality with respect to hs-cTnI groups defined by concentrations less than limit of detection (LoD; n=445), LoD to less than sex-specific upper reference limits (URLs; n=886), and greater then sex-specific URLs (n=309) is shown in Figure 2.…”
Section: Significance Statementmentioning
confidence: 98%
“…5 Therefore, cTn testing may be expected to show lower clinical specificity for MI in the setting of CKD. 5,7,[11][12][13] Direct comparison with performance criteria reported in non-CKD populations is difficult due to the lack of consistency used for diagnostic cutoff concentrations and other population parameters between studies. Understanding the diagnostic performance of cTn testing in the setting of CKD is important for clinicians given that patients with CKD are at higher risk of developing cardiovascular disease than the general population and that cardiovascular disease is the leading cause of death in those patients with ESRD.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A large number of studies have shown that in patients with end-stage renal disease (ESRD), both cTnI and cTnT are strong prognostic indicators for death of all causes and although cTnI increases less than cTnT, it is associated with a higher risk of mortality [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…149 Troponins and brain natriuretic peptides could have an additive value and should be further explored to assess their role in a comprehensive risk assessment for SCD. [150][151][152][153] There are very limited data regarding the prognostic significance of incidentally detected arrhythmias in CKD and ESKD. Identification of episodes of non-sustained ventricular tachycardia, frequent premature ventricular complexes, bradyarrhythmias and pauses may be useful in identifying patients at risk of SCD.…”
Section: Risk Factors For Sudden Cardiac Death In Chronic Kidney Disementioning
confidence: 99%